Relações entre perguntas dos estudantes e argumentações produzidas durante atividades em ciências nos anos iniciais - Costa, Daniela da (2020)
The importance of Science Teaching in the Early Years is characterized by the opportunity to develop questioning and arguing skills for these students. Therefore, developing activities that aim to understand the question and the arguments of these students becomes relevant for Science Teaching. Thus, this study seeks to answer the research question: How do students' initial questions relate to their arguments during activities in Science in the Early Years? The research occurs in two public schools of Basic Education in Porto Alegre, RS, in which the investigation was carried out with 3rd-year students of the Early Years and their respective teachers. Data collection occurs in two ways: with students, through an intervention activity called the birds and their beaks, and with teachers, through semi-structured interview. Both the intervention activity and the teachers' interviews were recorded and transcribed. Data analysis was performed using the Toulmin layout and Textual Discursive Analysis - ATD. Therefore, the possible answers to the aforementioned question were: a) the students' initial questions were causal, descriptive and predictive; b) students developed questions in the classroom categorized into questions associated with the contextualization of the content of the images and questions associated with the description of the characteristics of the images; c) the relationships between the students' initial questions and their arguments were predictive, contextualized and knowledge-expanding; and d) the perception of teachers regarding the activity that allowed the act of asking and arguing to students, two categories emerged: the factors that contribute to the promotion of questioning and argumentation in the classroom and the obstacles to the promotion of questioning and argumentation in the classroom